Homoeopathic prescribing in the late 19th century - Leary, Bernard (British Homeopathic Journal, 1994)
The discovery of the records of the London Homoeopathic Hospital dating from 1889 to 1923 has given the opportunity to study prescribing methods in the pre- and post-Kentian periods. In particular, it has given a detailed insight into late 19th century ideas which has not been available before. A pilot study has demonstrated the common remedies employed and their potencies. Further research is needed to determine, if possible, the reasons for selection of remedies and the relative efficacy of the 2 contrasting systems of prescription.